Numerical Investigation of Pores Statistic Distribution Influence on Porous Material Mechanical Behaviour - Danuta MIEDZIŃSKA (Engineering Transactions, 2017)
The aim of the work presented in the paper was to investigate the influence of pores statistic distribution used for porous material idealistic microstructure model generation on modelled material mechanical properties. Three distribution models were used: homogenous, normal and Weibull one. The model idea was based on the observation of SEM visualisation of shale rock structure which is characterized with dual porosity. The proposed models will be useful for mechanical behaviour of such structures prediction.